Analisis Kebijakan Penghapusan Tenaga Honorer di Lingkungan Pemerintah Kabupaten Bangkalan - Baiq Dessyazizah Destianikitha; Restu Agung Firdaus (Syntax Idea)
The elimination of honorary workers in the Bangkalan Regency Government has become a policy that raises various issues, both in terms of the welfare of honorary workers and the effectiveness of government administration. This policy was implemented due to the perceived low welfare of honorary workers, as there is no clear regulation regarding salary standards. Nevertheless, many honorary workers remain in their positions due to subjective happiness, such as life satisfaction, a sense of pride in being part of the government, and the hope of being appointed as civil servants (PNS) or government employees with work agreements (PPPK) without testing. However, the recruitment process for honorary workers that does not align with employee needs, based on prevailing regulations, has led to an uncontrolled surge in honorary workers. Additionally, this process is often associated with corruption, collusion, and nepotism, making the dismissal of honorary workers difficult. To address this issue, a strong commitment from both central and regional governments is necessary to ensure that the elimination of honorary workers is carried out gradually without creating new problems. The policy model applied in this process is a comprehensive rational policy model, which emphasizes decision-making based on actual needs while considering rationality to achieve efficiency and effectiveness in workforce governance in Bangkalan Regency.